Comparative analysis of machining and electropolishing for surface quality improvement of shape memory nitinol samples additively manufactured by laser powder bed fusion - Rodrigo Zapata Martínez; Shohom Bose-Bandyopadhyay; Alan Burl; Óscar Contreras-Almengor; Carlos Aguilar Vega; Kyle Saleeby; Thomas Kurfess; Andrés Díaz Lantada; Jon Molina-Aldareguia (Additive Manufacturing Letters)
Nickel-titanium (NiTi) or nitinol alloys exhibit high corrosion resistance, mechanical strength, biocompatibility, and smart properties, rendering them ideal materials for active biomedical devices. Traditional manufacturing techniques struggle with these alloys, prompting the adoption of Laser Powder Bed Fusion (L-PBF) as a viable alternative for producing geometrically challenging features. However, L-PBF inherently introduces geometric inconsistencies and surface defects, necessitating post-processing. Electropolishing and chemical etching, while effective for surface smoothing, result in non-conformal material removal, potentially altering the designed geometry. This study examines the use of machining as a post-processing method to achieve uniform material removal and maintain geometric fidelity. Planar spring-shaped actuators were fabricated via L-PBF and subsequently machined to their final geometry using a Computer Numerical Controlled (CNC) system. The actuators were assessed for geometric accuracy and shape memory properties. Machining of the actuators lead to a near homogeneous thickness of 300 µm in all cases, whereas the electropolished + chemically etched samples varied dramatically from <50 µm to over 400 µm in thickness. The findings demonstrate that CNC machining effectively enhances the geometric precision of L-PBF-manufactured NiTi components, while preserving shape memory characteristics. This research underscores the potential of integrating L-PBF with CNC machining to improve the precision and functionality of NiTi-based biomedical devices.